Do We Measure What Patients Feel?: An Analysis of Correspondence Between Somatosensory Modalities Upon Quantitative Sensory Testing and Self-reported Pain Experience. Issue 7 (July 2018) - Gierthmühlen, Janne; Binder, Andreas; Förster, Matti; Baron, Ralf
Abstract : Objectives: Hyperalgesia and allodynia are typical signs of neuropathic pain. Quantitative sensory testing (QST) is a validated tool to clinically assess these phenomena. However, whether QST reveals findings that are reported by the patients is unclear. The aim of this study was therefore to investigate the association between self-reported symptoms assessed with the painDETECT questionnaire (PDQ) with results of validated QST. Materials and Methods: PDQ and QST data of 96 patients with chronic neuropathic pain were analyzed. Questions upon presence of painful light touch, painful cold or heat, light pressure triggering pain, and numbness upon PDQ were compared with findings of dynamic mechanical allodynia, increased sensitivity to heat, cold, or pressure pain as well as loss of detection upon QST, respectively. Results: Self-reported pain symptoms upon PDQ showed only a small to moderate concordance with corresponding signs assessed upon QST, whereat the highest, but still only moderate association between self-reported symptoms and measured signs could be obtained for self-reported presence of painful light touch and dynamic mechanical allodynia upon QST. However, the positive and negative likelihood ratio to predict QST values with PDQ scores did not reach convincing values. Discussion: Results demonstrate that self-reported PDQ symptoms cannot predict abnormal QST values. The poor predictive power of the PDQ may depend on several factors based on possibility of comparison between PDQ and QST and also on methodical issues. Both, symptoms (questionnaires) and signs address complementary aspects of the pain experience and should be considered for diagnosis and treatment of neuropathic pain.